2023
DOI: 10.1021/acsomega.2c07472
|View full text |Cite
|
Sign up to set email alerts
|

Ion Kinetics and Capacity Tailoring in Stacked Graphdiyne by Functionalization

Abstract: Stacked two-dimensional (2D) materials as bulk materials are more practical to be anodes of Li-ion batteries than their monolayers due to the easier operation, while the ion kinetics and capacity are usually deteriorated by the geometric constraint in stacked structures. Herein, we perform first-principles calculations to explore anode performances of the stacked graphdiyne (GDY) where the functional group is intercalated to enlarge the interlayer distance. Compared to the monolayer GDY, which has a diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The pathways for CI-NEB calculations are usually straight between the initial and final positions. Similar diffusion pathways within layers and between layers ,, can be found in previous studies. For the intralayer zinc-ion migration, three pathways are considered, and the corresponding diffusion barriers are 0.29, 0.24, and 0.23 eV in Figure d.…”
Section: Resultssupporting
confidence: 83%
“…The pathways for CI-NEB calculations are usually straight between the initial and final positions. Similar diffusion pathways within layers and between layers ,, can be found in previous studies. For the intralayer zinc-ion migration, three pathways are considered, and the corresponding diffusion barriers are 0.29, 0.24, and 0.23 eV in Figure d.…”
Section: Resultssupporting
confidence: 83%
“…The voltages of these doped GDYs decrease from about 2 to almost 0 V as the capacities approach the upper limits. The average voltages are in the range of 0.38− 0.47 V, smaller than the average voltage of 0.74 V in the stacked GDY, 50 which may be because of the stronger adsorption and lower capacity of Li in the intercalation site.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…Then, as the path from S 2 to S 3 passes through an acetylenic linkage, the diffusion barriers increase to 0.36, 0.34, and 0.31 eV. The diffusion barrier of Li on a monolayer GDY is 0.315−0.51 eV, 24,50 meaning the dopants do not significantly affect the Li kinetics. Then, comparing with the 0.47−0.48 eV diffusion barrier of Li on graphene, 51 the anodes with the doped GDYs are expected to have better rate performance than graphene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The lower barrier of the internal FS might result from the adjacent perfect GDY layer, which offers a relatively flat path for Li atom diffusion. Comparing to the intercalation and surface sites, where the energy barriers are 0.638 and 0.315 eV, 29 the FS sites have moderate resistance for the migration of Li atoms. We summarize the anode performances of internal and external FSs and compare them to that of perfect GDYs in Table 1.…”
Section: Resultsmentioning
confidence: 95%
“…The AB stacking mode is selected because our previous research showed that AB stacking has good structural stability. 29 By removing half of the atoms in a layer of the GDY, the internal FS model can be gained, which is sandwiched between perfect GDY layers. Then, for the external FS, the lattice of the 2 × 2 supercell is added to a 10 Å vacuum layer in the in-plane direction instead of deleting any atoms, resulting in the surface adjacent to the vacuum layer becoming the external FS.…”
Section: Resultsmentioning
confidence: 99%